Synthesis and Cytotoxicity Study of Some Acetylisatins and Diazobiphenyls - Hossain, Mohammad Mamun; Shaha, Sakanta Kumar; Aziz, Foysal; Khan, Rahat; Hossain, Md Mahabub (Dhaka University Journal of Pharmaceutical Sciences, 2011)
Nitrogenous heterocyclic compounds, oxindoles especially isatins and related heterocyles have excellent antifungal, anti-inflammatory, antimicrobial and anticancer activities. Oxindoles keto lactams (1-3) were synthesized according to modified Sandmayer method and their N-acetylated compounds (4-6) gave diazo-biphenyls (7-10) through ring cleavage and consequent cyclization reaction. Bis-amide (11), and Schiff-base (12) were synthesized from oxindoles respectively. The investigation of cytotoxicity of the synthesized compounds was carried out against brine shrimp lethality bioassay. In our present investigation some of the synthesized compounds such as halogen substituted acetylisatins (4-6) and the ring extended diazo-biphenyls, (7-10) have been shown to exhibit strong cytotoxic effect. Key words: diazo-biphenyls; oxindoles; cytotoxicity; brine shrimp DOI: 10.3329/dujps.v9i1.7423 Dhaka Univ. J. Pharm. Sci. 9(1): 1-6, 2010 (June)